A case of aspergillotic orbital apex syndrome diagnosed by an additional intraorbital biopsy after nasal endoscopy. Issue 6 (25th September 2018) - Matsumoto, Namiko; Sato, Kota; Tadokoro, Koh; Takahashi, Yoshiaki; Yunoki, Taijun; Takemoto, Mami; Hishikawa, Nozomi; Ohta, Yasuyuki; Yamashita, Toru; Fujii, Kentaro; Ichikawa, Tomotsugu; Date, Isao; et al.
Abstract: The prompt and accurate diagnosis of orbital apex syndrome (OAS) is very important because of its fatality. Here we report an old man with aspergillotic OAS diagnosed after two biopsies by nasal endoscopy and craniotomy. Only craniotomy leads to the appropriate diagnosis, suggesting an immediate need of additional biopsy for the accurate diagnosis and saving the patient.